교실목표 및 수업환경 지각과 도움요청 행동의 관계 - 조준수(Jun Soo Cho) (Korean Journal of child studies, 2001)
The present study examined the relation between academic help-seeking behaviors and classroom context based on students' perceptions of various classroom goals stressed by their teachers and their perceived teacher support for seeking help. The 305 subjects were 5th grade students(162 boys and 143 girls) of an elementary school in Gwangyang. The students completed a questionnaire. Data were analyzed by $2{×}2$ ANOVA. Results showed that students' help-seeking behaviors were influenced by their teachers' goal orientation and perceived teacher support for seeking help. The results of this study suggest that perceived teacher support for seeking help may be expecially important for some students who could use instrumental help to continue task engagement, and teachers' learning-focused goal orientation is an important variable of instrumental help-seeking behavior.